Dural sinus thrombosis following epidural analgesia for delivery: a clinical case - Dornelles,Marco Aurelio (2018)
Abstract Background and objectives: Neurological complications of spinal anesthesia are rare conditions. Headache caused by low pressure of the cerebrospinal fluid is one of the most frequent, which occurs after post-dural puncture. A comprehensive history and physical exam must be carried out before making the diagnosis of Post-Dural Puncture Headache (PDPH) and additional tests are necessary to exclude the possibility of developing serious neurological complications such as Dural Sinus Thrombosis (DST). According to the Case Report a differential diagnosis between Dural Sinus Thrombosis with PDPH is discussed. Case report: A 22 year-old lady, ASA Physical Status Class I was admitted at 39 weeks of gestation for delivery. For labor pain relief she requested epidural for analgesia, but unfortunately accidental dural puncture occurred. She developed an occipital headache and neck pain in the second day postpartum which was relieved by both lying down and supporting treatment such as rehydration, analgesics and caffeine. On day third postpartum she was discharged without complaints. On day fifth postpartum the pain returned and became more intense and less responsive to oral analgesics. She was admitted to the hospital to do a complete neurological and image investigation that showed a lesion consistent with the diagnosis of cortical vein thrombosis and Dural Sinus Thrombosis (DST). She was treated with oral anticoagulants. After two days, a repeated magnetic resonance image (MRI) showed partial canalization of the central sinus thrombus. The patient was discharged from hospital five days after her admission without any of the initial symptoms. Conclusion: The report describes a patient who developed severe headache following continuous epidural analgesia for delivery. Initially it was diagnosed as PDPH, however with the aid of MRI the diagnosis of DST was later established and treated. DST is a rare condition and is often underdiagnosed. Because of its potentially lethal complications, it should always be considered in acute headache differential diagnosis.